2012
DOI: 10.1126/science.1214318
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in a Chloride Channel Subunit Confers Avermectin Resistance in C. elegans

Abstract: Resistance of nematodes to anthelmintics such as avermectins has emerged as a major global health and agricultural problem, but genes conferring natural resistance to avermectins are unknown. We show that a naturally occurring four amino-acid deletion in the ligand-binding domain of GLC-1, the alpha-subunit of a glutamate-gated chloride channel, confers resistance to avermectins in the model nematode Caenorhabditis elegans. We also find that the same variant confers resistance to the avermectin-producing bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
196
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(205 citation statements)
references
References 44 publications
3
196
6
Order By: Relevance
“…Moreover, the behavior identified here need not be the most important one in natural settings; it may represent one of several behavioral and physiological responses that facilitate adaptation to different environments. Balancing selection may be fairly common throughout the C. elegans genome: a recent report identified 61 highly divergent regions likely to be under balancing selection that segregate among wild strains of C. elegans, including a second region 200 kb from roam-1 24,29 (Extended Data Figure 8). The composition of these regions is biased toward particular gene classes including chemoreceptors, which may act as hotspots of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the behavior identified here need not be the most important one in natural settings; it may represent one of several behavioral and physiological responses that facilitate adaptation to different environments. Balancing selection may be fairly common throughout the C. elegans genome: a recent report identified 61 highly divergent regions likely to be under balancing selection that segregate among wild strains of C. elegans, including a second region 200 kb from roam-1 24,29 (Extended Data Figure 8). The composition of these regions is biased toward particular gene classes including chemoreceptors, which may act as hotspots of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Hco-avr-14 and Hco-glc-5 are members of the H. contortus glutamate-gated chloride channel (GLC) family (Wolstenholme and Rogers, 2005;McCavera et al, 2007;Laing et al, 2013). Three members of this family in Caenorhabditis elegans -Cel-glc-1, Cel-avr-14 and Cel-avr-15 -have been shown to be ivermectin targets by genetic mutation and complementation studies (Dent et al, 2000;Ghosh et al, 2012). The H. contortus homologue of Cel-avr-14 -Hco-avr-14 -was implicated in ivermectin resistance by its ability to rescue ivermectin susceptibility when heterologously expressed in C. elegans, suggesting it is an ivermectin target in the parasite (McCavera et al, 2007(McCavera et al, , 2009Glendinning et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed unexpected variation in both fertility and oocyte function in wild strains of C . elegans upon exposure to high temperature [30], in responses to the anthelmintic avermectin [31], and in mitotic spindle structure and function [32]. The effects of environmental and chemical stressors, including CuO NPs, to C .…”
Section: Introductionmentioning
confidence: 99%